Tingkat Kepuasan Pelanggan dari Kualitas Jasa Layanan - Juwono, Onny (Journal the Winners: Economics, Business, Management, and Information System Journal, 2009)
Recently, consumers become more critical. They criticize whenever they found the quality of service offered was not according to what had already been promised. On the other hand, quality of service became the sword of marketing program. Thus, these two elements go hand in hand to retain consumers. This research aims to answer some problems regarding quality of service of a photo developer retail outlet. Data gathered from consumers were analyzed by using validity, realibility and weighted mean to indicate the response of consumers towards all elements embeeded within the business. The research results showed that consumers found satisfied with the service given. However, the study suggested several steps to maintain customer satisfaction.